2019
DOI: 10.1155/2019/9483647
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Profile of CD4+ T-Cell-Associated Cytokines/Chemokines following Murine Myocardial Infarction/Reperfusion

Abstract: CD4+ T-cells play crucial roles in the injured heart. However, the way in which different CD4+ T subtypes function in the myocardial infarction/reperfusion (MI/R) heart is still poorly understood. We aimed to detect the dynamic profile of distinct CD4+ subpopulation-associated cytokines/chemokines by relying on a closed-chest acute murine MI/R model. The protein levels of 26 CD4+ T-cell-associated cytokines/chemokines were detected in the heart tissues and serum of mice at day 7 and day 14 post-MI/R or sham su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 68 publications
(80 reference statements)
2
25
0
1
Order By: Relevance
“…Thus, IL-9 may be the novel contributing factor in atherosclerosis [16][17][18]. Recent studies also reported that Th9/IL-9 levels were increased in patients with aortic dissection and in myocardial infarction/reperfusion mice [19,20]. In coxsackievirus B3-induced myocarditis, IL-9 reduces viral replication and thus reduces myocardial injury [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IL-9 may be the novel contributing factor in atherosclerosis [16][17][18]. Recent studies also reported that Th9/IL-9 levels were increased in patients with aortic dissection and in myocardial infarction/reperfusion mice [19,20]. In coxsackievirus B3-induced myocarditis, IL-9 reduces viral replication and thus reduces myocardial injury [21].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the proinflammatory EVs during IR helps break the inflammation‐injury circle and eventually alleviate the cardiac injury. In addition to local inflammation induced by direct cardiac injury, it is still a mystery that heart disease is usually accompanied by a systemic low‐grade inflammation (Scally et al., 2019; Yuan et al., 2019). As shown in our study, IR injury not only increased the inflammation in the heart but also in distant organs, and GW4869 treatment dampened the systemic inflammation in IR mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activated T cells were elevated in patients with UAP and AMI compared with SAP, suggesting that T‐cell immunity may be involved in the mechanisms of coronary instability (6). CD8 + T cells are accumulated and activated in the necrotic myocardium of AMI and contributed to myocardial injury (7, 8), while CD4 + T cells also play modulatory roles in injury and healing post‐myocardial infarction via secretion of associated cytokines (9, 10).…”
mentioning
confidence: 99%